Adsorption for copper(II) ion with chitosan-SP/PET composite adsorbent enhanced by electric field - Yunfei Song; Aiqun Kong; Yanhong Ji; Benqiao He; Hong Wang; Jianxin Li (Adsorption Science & Technology)
A method combining adsorption with electric field-driven ion enrichment to remove the trace metal ions in wastewater was investigated. Composite adsorbent prepared from chitosan (CS) and sodium phytate (SP) supported into polyethylene glycol terephthalate (PET) nonwoven fabric by nonsolvent induced phase separation was employed and located near the cathode in a pair of titanium plate electrodes. Results showed the removal rate of copper ions (Cu(II)) adsorbed onto CS-SP/PET adsorbent was increased from 56% to 88% for 10 mg L −1 Cu(II) solution when the applied voltage was from 0 to 1.2 V. The adsorption behavior was well correlated with the Langmuir isotherm model. And adsorption process fitted well for pseudo-second-order kinetic equation, suggesting that chemical adsorption was rate-limiting step. And the energy consumption was economical, about 4.35 × 10 −3 kW·h for 1 m 3 of water with 10 mg L −1 Cu(II). It was suggested that the adsorption performance for Cu(II) with CS-SP/PET adsorbent was enhanced due to the enrichment of Cu(II) under electric field. This work provides a new way to remove trace heavy metal ions from wastewater.